Chemical Composition, Antiviral and Cytotoxic Activities of Essential Oil from Cyperus rotundus Growing in Egypt: Evidence from Chemometrics Analysis. Issue 4 (3rd July 2020) - Samra, Reham M.; Soliman, Amal F.; Zaki, Ahmed A.; El-Gendy, Abdel Nasser; Hassan, Madiha A.; Zaghloul, Ahmed M.
Abstract: The essential oil of Egyptian Cyperus rotundus rhizomes was obtained by hydrodistillation and analyzed by GC/MS. The oil is composed mainly of oxygenated sesquiterpenes. Thirty-seven compounds were identified including, humulene epoxide (38.43 %) and caryophyllene oxide (21.03 %) as major components. Correlations between different C. rotundus essential oils from Egypt and other regions were studied based on its chemical composition through principal components analysis and agglomerative hierarchical clustering. The oil was tested for its antiviral activity against hepatitis A, herpes simplex type 1, and coxsackie viruses at non-cytotoxic concentration. The oil was also evaluated for its cytotoxicity on hepatic, breast, and prostate carcinomas. It showed a very weak activity against tested viruses with percent protection 7.98, 14.21 and 8.79 %, respectively at a maximum non-toxic concentration of 125 μg/mL and it exhibited moderate cytotoxicity against hepatic and breast cancer cell lines with IC50 values of 204.1±1.25 and 170.8±0.567 μg/mL, respectively. The oil did not exhibit any cytotoxicity against the prostate cancer cell line.